Application of discrete Fourier transform to inverse heat conduction problem regularization. Issue 1 (2nd January 2018) - Frąckowiak, Andrzej; Ciałkowski, Michał
Abstract : Purpose: This paper aims to present the Cauchy problem for the Laplace's equation for profiles of gas turbine blades with one and three cooling channels. The distribution of heat transfer coefficient and temperature on the outer boundary of the blade are known. On this basis, the temperature on inner surfaces of the blade (the walls of cooling channels) is determined. Design/methodology/approach: Such posed inverse problem was solved using the finite element method in the domain of the discrete Fourier transform (DFT). Findings: Calculations indicate that the regularization in the domain of the DFT enables obtaining a stable solution to the inverse problem. In the example under consideration, problems with reconstruction constant temperature, assumed on the outer boundary of the blade, in the vicinity of the trailing and leading edges occurred. Originality/value: The application of DFT in connection with regularization is an original achievement presented in this study.